The Influence of the Implementation of the Self-Directed Learning (SDL) Learning Model Assisted by Blended Learning on the Learning Outcomes of Environmental Chemistry Students - Pratimi, Renda Suri (Lembaga Riset Mutiara Akbar, 2024)
This study aims to examine the effect of implementing the Self-directed learning learning model assisted by blended learning on the cognitive learning outcomes of Environmental Chemistry Students. This study focuses on seeing the extent to which the use of the self-directed learning model, namely self-efficacy, self-control and desire for learning assisted by blended learning, influences cognitive learning outcomes. This research method uses a quasi-experimental design with a Post Test Only Control Design involving a control group and an experimental group as samples. The independent variable in this study is a learning model consisting of two dimensions, namely self-directed learning (SDL) assisted by blended learning in the experimental group and learning with lectures assisted by blended learning in the control group. The dependent variables include cognitive learning outcomes, and the results of the SDL component test. The research procedure begins with the stages of preparing materials, samples, and environmental conditions, then continues with making instruments to collecting data. Cognitive learning outcome data were analyzed using the SPSS t test which showed that the self-directed learning model assisted by blended learning influenced the cognitive learning outcomes of students in learning environmental chemistry at the Doe Islamic Study Institute. Self-directed learning involves the discovery and solving of problems that are scientifically and socially important. The SDL model invites students to participate more actively independently, in a structured way in critical and creative thinking in presenting solutions, thus motivating students to be involved independently in the entire learning process.